2020
DOI: 10.1002/term.3153
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid released from poly(ε‐caprolactone) fibers as a treatment platform for spinal cord injury

Abstract: Spinal cord injury (SCI) is characterized by a primary mechanical phase of injury, resulting in physical tissue damage, and a secondary pathological phase, characterized by biochemical processes contributing to inflammation, neuronal death, and axonal demyelination. Glutamate‐induced excitotoxicity (GIE), in which excess glutamate is released into synapses and overstimulates glutamate receptors, is a major event in secondary SCI. GIE leads to mitochondrial damage and dysfunction, release of reactive oxygen spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Using PCL as a drug delivery system to deliver uric acid, Singh and coworkers successfully protected spinal cord tissue from excitotoxic injury in an in vitro injury model 250 .…”
Section: Synthetic Polymeric Materialsmentioning
confidence: 99%
“…Using PCL as a drug delivery system to deliver uric acid, Singh and coworkers successfully protected spinal cord tissue from excitotoxic injury in an in vitro injury model 250 .…”
Section: Synthetic Polymeric Materialsmentioning
confidence: 99%
“…However, when administered in high doses it can lead to kidney toxicity and gout (Fathallah-Shaykh & Cramer, 2014). Therefore, a localized delivery of uric acid to the spinal cord via electrospun fibers was proposed by Singh et al (2021).The release of uric acid from PCL fibers was calculated by measuring the drop in pH over 2 h of incubation in PBS. In an organotypic SCI model, treatment of spinal cord slices with uric acid-loaded fibers reduced glutamate-induced cell death and ROS in both dorsal and ventral regions, suggesting that local treatment with uric acid protects spinal cord tissue from glutamate-induced excitotoxicity.…”
Section: Spinal Cord Injurymentioning
confidence: 99%
“…However, when administered in high doses it can lead to kidney toxicity and gout (Fathallah‐Shaykh & Cramer, 2014). Therefore, a localized delivery of uric acid to the spinal cord via electrospun fibers was proposed by Singh et al (2021). The release of uric acid from PCL fibers was calculated by measuring the drop in pH over 2 h of incubation in PBS.…”
Section: Examples Of Drug‐loaded Electrospun Scaffold In Neural Injuriesmentioning
confidence: 99%
“…•− and HO • and is the major antioxidant in body fluids and preserves neuronal viability in preclinical models of SCI [36]. GPX is a selenium-(Se-) dependent enzyme and it was shown that Se nanoparticles could reverse oxidative stress-induced SCI in rats [37].…”
Section: •−mentioning
confidence: 99%